MODEL MATEMATIKA ADSORPSI ZEOLIT ALAM - Adi Saputro,E, Pujiastuti,C (Jurnal Teknik Kimia, 2008)
Waste Water of electroplating industry contains various dangerous metal ion wich aredangerous for environment, for example Zinc and Nickel. The concentration of those heavy metal ioncan exeed quality standard value of waste water, therefore it needs to be processed before releasedto environmentIn this research, processing of Waste Water of electroplating industry was done by usingzeolite as metal ion adsorbent of Zn. This Research was done by using baffle tank .The purpose of this research was to get mathematics equation of Langmuir and of Freundlichzeolite absorption to Zn ion.. Specified conditions : waste water volume 200ml, baffle rotation 100rpm . with variable done were : Zeolite size, squealer time and zeolite weight. Waste water with zeolitewere swirled during certaintimer; then filtered and the content of Zn ion of the filtrate was analyzed.Early Concentration from waste water ( Zn 2+) is : 113,37 mg / lEquation acquire in this research for zeolite size 40 mesh were as follows :Freundlich equation : ln ( x / m) = 0,3268 c ln - 0,8284, with correlation coefficient of R2 = 0,9262 .While Langmuir equation was :24 , 169 485 , 25) / (+ − =  Keyword : zeolite, waste of electroplating, adsorption, Zn ionwith R2 = 0,99. Based on equation above, zeolite requirement for reducing the content of Zn in electroplating waste water can be calculated, to the wantedconcentrationC m xC